ANALISIS TERHADAP IMPLEMENTASI HUKUM INTERNASIONAL DALAM PERLINDUNGAN LINGKUNGAN GLOBAL (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Global environmental protection has emerged as a strategic issue in modern international law. As the impacts of climate change, environmental degradation, and biodiversity loss intensify, the international community recognizes the urgency of cross-border cooperation to ensure planetary sustainability. Treaties such as the Kyoto Protocol, the Paris Agreement, and the Kunming-Montreal Global Biodiversity Framework set global norms and standards. However, their implementation remains hampered by weak law enforcement systems, inequalities in state capacities, and conflicting domestic interests. This study uses a normative juridical approach by analyzing key international legal instruments and their implementation in national contexts. The research finds that while regulatory frameworks have evolved, political will, technological limitations, and economic priorities still undermine international law’s effectiveness. Therefore, strengthening international mechanisms, enhancing transparency, and fostering multi-actor synergy are essential to ensure successful global environmental protection.